2021
DOI: 10.1111/dom.14550
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood glucose variability in ambulatory glucose profile and standardized continuous glucose monitoring metrics: Subanalysis of a prospective cohort study

Abstract: Aim: To clarify the relationship between ambulatory glucose profile (AGP) indexes and standardized continuous glucose monitoring (CGM) metrics in patients with type 2 diabetes (T2D).Methods: This is an exploratory, cross-sectional analysis of baseline data collected from a prospective, multicentre, 5-year follow-up observational study conducted and published previously by our group. The study participants were 999 outpatients with T2D who used CGM at baseline, and had no apparent history of cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The FreeStyle Libre Pro (FLP) (Abbott Japan, Tokyo, Japan) CGM (FLP-CGM) device, which measures glucose levels every 15 minutes for up to 14 days, was used as previously reported ( 15 , 17-19 ). Other than wearing the FLP-CGM, there were no restrictions on participants’ daily lives.…”
Section: Methodsmentioning
confidence: 99%
“…The FreeStyle Libre Pro (FLP) (Abbott Japan, Tokyo, Japan) CGM (FLP-CGM) device, which measures glucose levels every 15 minutes for up to 14 days, was used as previously reported ( 15 , 17-19 ). Other than wearing the FLP-CGM, there were no restrictions on participants’ daily lives.…”
Section: Methodsmentioning
confidence: 99%
“…Tokutsu et al . 21 found that an average IQR cutoff of 2.13 mmol/L achieved TIR >70%, whereas 1.85 mmol/L resulted in TIR >90%.…”
Section: Metrics Of Glycemic Variability: Is Less Really More?mentioning
confidence: 96%
“…Ambulatory glucose profile condenses CGM data into a 24‐h representation, and IQR, represented by the 25th to 75th percentile trend lines on ambulatory glucose profile, serves as a powerful visual tool for assessing GV 19,20 . Additionally, robust correlations exist between average IQR and within‐day GV metrics, including SD and CV, as well as interday variations 21 . A significant IQR warrants an exploration of the factors influencing both interday and intraday GV in clinical settings.…”
Section: Metrics Of Glycemic Variability: Is Less Really More?mentioning
confidence: 99%
See 1 more Smart Citation